Hubungan Sistem Reward dan Punishment Pada Sikap Disiplin Mata Pelajaran Sejarah - Anny Wahyuni; Melita Anggriani Situmorang; Yundi Fitrah (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This study aims to describe the effect of Reward and Punishment on the behavior of students learning history discipline Class XII IPS SMA Negeri 8 Jambi. This study in Class XII IPS SMA Negeri 8 Jambi. Research Data obtained by distributing questionnaires to students of Class XII IPS SMA Negeri 8 Jambi city (as the main data). After the questionnaire is filled, the data is analyzed quantitatively with correlational research design. The results showed the results : (1) there is no effect of reward to the behavior of students learning history discipline Class XII IPS SMA Negeri 8 Jambi. Based on the T test obtained tcount < ttable (1.779<1.977). (2) there is the effect of punishment on the behavior of students studying history discipline Class XII IPS SMA Negeri 8 Jambi. Based on the T test obtained tcount > ttable (6.667>1.977), which means that the more firm and appropriate punishment given for the mistakes of Students, Students ' Disciplinary behavior will also increase. (3) there is the effect of reward and punishment on the behavior of students learning history discipline Class XII IPS SMA Negeri 8 Jambi. Based on the F test obtained Fcount > Ftable (62.148> 3.06), meaning that the more attractive the reward given and the stricter the punishment applied to students will further improve student discipline in learning.